Some ideas concerning public relations in sports organizations - Raposo, Ana Luísa Canelas Rasquilho (2018)
The specific research question that this paper will be addressing may be summarised as an interrogation about the role that the communication professionals are called to fulfill in the sports federations in Portugal. Do the communication professionals have operational and strategic responsibilities in the Portuguese sports federations? How do these organizations understand the concept of "strategic communication"? Is institutional or corporate communications still understood as a function that belongs exclusively to the realm of private companies? Under the umbrella concept of strategic responsibilities, we've considered aspects as the definition of the communication priorities in a strategic and planned way or the mapping and management of the stakeholders. Questions as the existence of a media relations plan or a risk and crisis communication plan were also addressed. Under the idea of a more operational approach, we've considered aspects that have to do with events and actions that are dealt in a merely responsive or casuistical way.